2018
DOI: 10.1017/s0047279417000794
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Low Uptake of Direct Payments in Residential Care: Findings from the Evaluation of the Direct Payments in Residential Care Trailblazers

Abstract: In 2012, the Government invited local councils in England to participate in a pilot programme to test direct payments in residential care. While the programme was set up to allow for comprehensive summative evaluation, the uptake of direct payments in residential care was substantially lower than anticipated, with only 40 people in receipt of one at the end of the programme. Drawing on qualitative data collected for the evaluation, this paper aims to understand better the barriers to implementing direct paymen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The plan was that the remaining local authorities would learn from the experience of the trailblazers and that direct payments would be made available to all residents in care homes from April 2016. However, in 2015 (Ettelt et al, 2017). The aims of the evaluation were to understand how direct payments could be introduced in residential care and to assess the potential impact of direct payments on care home residents, their families, local authorities and care home providers.…”
Section: Introductionmentioning
confidence: 99%
“…The plan was that the remaining local authorities would learn from the experience of the trailblazers and that direct payments would be made available to all residents in care homes from April 2016. However, in 2015 (Ettelt et al, 2017). The aims of the evaluation were to understand how direct payments could be introduced in residential care and to assess the potential impact of direct payments on care home residents, their families, local authorities and care home providers.…”
Section: Introductionmentioning
confidence: 99%
“…The model of funding recommended by the jurors (a split between core and discretionary services) has some similarities to one of the models trialled within the pilot of direct payments in residential care in England described earlier. 10 The evaluation of the program found that this particular model of funding was however more difficult to implement than the other models and, as noted, that costs of establishing the scheme were high as was the administrative work involved in managing payments and organizing activities for all models. Uptake of direct payments in the English pilot program was poor and residents will be less likely to choose this model of care if it is associated with considerable administrative costs.…”
Section: Discussionmentioning
confidence: 99%
“…While the main recommendation relates to redistribution of existing funding to core and discretionary funding, there will be administrative costs in establishing this as found within other programs. 10 As there are issues around risk management, extensive work would need to be undertaken to detail the rights and responsibilities of the provider, the resident and their families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choice policies are currently being extended via the use of personal budgets for residential care, where users are allocated direct payments or managed budgets to allow them greater control over provider and service choice (Ettelt et al . 2015). A large proportion of people funding their own care have always been able to select their provider of choice, subject to their own financial limitations.…”
Section: Introductionmentioning
confidence: 99%